How prosody constitutes the actions of formulations in courtrooms - Ana Cristina Ostermann; Daniela Negraes Pinheiro Andrade; Minéia Frezza (Working Papers em Linguística)
Based on the theoretical and methodological perspectives of Conversation Analysis and Interactional Linguistics, this study investigates how the prosodic feature pitch contributes to the formation and ascription of actions in court hearings, in particular, in practices of formulation. The analysis reveals that variations of pitch in the practice of formulating are intrinsically related to the different locally and situated actions performed: checking understandings and challenging the interlocutor.